Ensemble coding of multiple facial expressions is not affected by attentional load - Yujuan Liu; Luyan Ji (BMC Psychology, 2024)
Abstract Human observers can extract the mean emotion from multiple faces rapidly and precisely. However, whether attention is required in the ensemble coding of facial expressions remains debated. In this study, we examined the effect of attentional load on mean emotion processing with the dual-task paradigm. Individual emotion processing was also investigated as the control task. In the experiment, the letter string and a set of four happy or angry faces of various emotional intensities were shown. Participants had to complete the string task first, judging either the string color (low attention load) or the presence of the target letter (high attention load). Then a cue appeared indicating whether the secondary task was to evaluate the mean emotion of the faces or the emotion of the cued single face, and participants made their judgments on the visual analog scale. The results showed that compared with the color task, the letter task had a longer response time and lower accuracy, which verified the valid manipulation of the attention loads. More importantly, there was no significant difference in averaging performance between the low and high attention loads. By contrast, the individual face processing was impaired under the high attention load relative to the low attentional load. In addition, the advantage of extracting mean emotion over individual emotion was larger under the high attentional load. These results support the power of averaging and provide new evidence that a rather small amount of attention is needed in the ensemble coding of multiple facial expressions.